Challenges and Opportunities in Implementing a Digital Curriculum in Schools: A Perspective on Teacher Readiness, Infrastructure, and Students’ Learning Behavior - Fairi, Nabiilah Nurrahmah; Diwangga, Bandu Putri; Alpia, Nurul; Destiyan, Sherly (TOFEDU: The Future of Education Journal, 2025)
Digital transformation and advances in artificial intelligence have brought significant impacts to the field of education, including in Indonesia. This study aims to analyze the challenges and opportunities in implementing a digital curriculum from the perspectives of teacher readiness, infrastructure, and students’ learning behavior. The research employed a qualitative literature review with a population consisting of national and international journals, educational policy documents, and reports from reputable institutions. The sample was selected purposively from sources specifically discussing the implementation of the digital curriculum in Indonesia. Data were collected using recording sheets and analyzed using thematic content analysis with data triangulation to ensure validity. The findings indicate that teacher readiness is the main obstacle due to limited digital-based pedagogical knowledge, and infrastructure inequality hinders equitable access, particularly in remote areas. Technology positively influences students’ motivation and collaboration, yet it also leads to negative distractions. In conclusion, strengthening teacher competencies, equalizing infrastructure, and establishing digital ethics regulations are crucial for the successful implementation of the digital curriculum. Future research is recommended to integrate qualitative and empirical data for more comprehensive results.